2014
DOI: 10.1111/hae.12603
|View full text |Cite
|
Sign up to set email alerts
|

Research in haemophilia B – approaching the request for high evidence levels in a rare disease

Abstract: Payers in European countries request studies with high levels of evidence for decision making also for rare diseases like haemophilia B (HB). The objective of the study was to determine the status quo of current studies in HB regarding the overall level of evidence generated. The methods used for performing the study were systematic literature research in EMBASE and MEDLINE, search terms 'HB' and 'factor IX' (FIX). The inclusion criteria were journal articles (JA), conference abstracts (CA), English language, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Data regarding the use of prophylaxis treatment regimens in patients with haemophilia B are limited. A recent systematic literature review of publications from 2009 to 2013 revealed that the previous study by Valentino et al was the only randomized study comparing on-demand treatment with prophylaxis regimens in haemophilia B patients [13]. However, prophylaxis regimens have prevented joint damage in patients with severe haemophilia A in several studies [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Data regarding the use of prophylaxis treatment regimens in patients with haemophilia B are limited. A recent systematic literature review of publications from 2009 to 2013 revealed that the previous study by Valentino et al was the only randomized study comparing on-demand treatment with prophylaxis regimens in haemophilia B patients [13]. However, prophylaxis regimens have prevented joint damage in patients with severe haemophilia A in several studies [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Haemophilia B is a rare bleeding disorder caused by reduced or absent clotting factor IX (FIX) with an X-linked inheritance. 1 Haemophilia B is categorised as mild (FIX:C >0.05-0.40 IU/mL), moderate (FIX:C 0.01-0.05 IU/mL) or severe (FIX:C <0.01 IU/mL), and the bleeding phenotype is related to baseline plasma FIX levels. 2 Ireland has higher rates of haemophilia B than many countries, with a prevalence of 8 per 100,000 males, which is double the recently reported prevalence of 3.8 per 100,000 males from other national registries.…”
Section: Introductionmentioning
confidence: 99%
“…Haemophilia B is a rare bleeding disorder caused by reduced or absent clotting factor IX (FIX) with an X‐linked inheritance 1 . Haemophilia B is categorised as mild (FIX:C >0.05‐0.40 IU/mL), moderate (FIX:C 0.01‐0.05 IU/mL) or severe (FIX:C <0.01 IU/mL), and the bleeding phenotype is related to baseline plasma FIX levels 2 .…”
Section: Introductionmentioning
confidence: 99%